2018
DOI: 10.1016/j.bioelechem.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial desalination cell with sulfonated sodium poly(ether ether ketone) as cation exchange membranes for enhancing power generation and salt reduction

Abstract: Microbial desalination cell (MDC) is a bioelectrochemical system capable of oxidizing organics, generating electricity, while reducing the salinity content of brine streams. As it is designed, anion and cation exchange membranes play an important role on the selective removal of ions from the desalination chamber. In this work, sulfonated sodium (Na) poly(ether ether ketone) (SPEEK) cation exchange membranes (CEM) were tested in combination with quaternary ammonium chloride poly(2,6-dimethyl 1,4-phenylene oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 66 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Increased desalination efficiency of 72.6 ± 3.0% was achieved for a NaCl concentration of 20 g/L. Moruno and coworkers [414] reported sulfonated sodium poly(ether ketone) cation exchange membranes and quaternary ammonium chloride poly(2,6-dimethyl 1,4-phenylene oxide) anion exchange membranes. (AEM).…”
Section: New Emerging Trendsmentioning
confidence: 99%
“…Increased desalination efficiency of 72.6 ± 3.0% was achieved for a NaCl concentration of 20 g/L. Moruno and coworkers [414] reported sulfonated sodium poly(ether ketone) cation exchange membranes and quaternary ammonium chloride poly(2,6-dimethyl 1,4-phenylene oxide) anion exchange membranes. (AEM).…”
Section: New Emerging Trendsmentioning
confidence: 99%
“…A porous membrane's only advantage is its low internal resistance 181 . Moruno et al 8,182 have shown that ionizing commercially available polymers produce thinner and more conductive AEMs and CEMs that can improve the desalination rate and power output for MDC compared to baseline studies utilizing thick CEMs and AEMs with low ionic conductivity. To increase current density and power, the membrane's internal resistance must be as low as possible.…”
Section: Membranementioning
confidence: 99%
“…The technology of desalination has played a crucial role in this area since the 1960s. In recent decades, the number of desalination plants has steadily increased 8 . The commercial use of desalination plants started around 1869 in England to supply drinking water for ships.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodeionization (EDI) is widely used to obtain high-purity water, which is especially important in industrial processes, food processing, and pharmaceuticals. , Electrochemical separation technique is increasingly analyzed in terms of its possible use in bioconversion processes. , Boontawan et al used the electrodeionization module in the bioproduction of lactic acid as an element that increases efficiency by the continuous separation of lactate ions from the bioreactor . Bioconversion was carried out with glucose as a carbon source and Pediococcus pentosaceus strain with a homofermentative property and a high stereoselectivity of L­(+)-lactic acid.…”
Section: Introductionmentioning
confidence: 99%